Decentralizing IT with the adoption of End-User Development: two case studies - Melo, Claudia de O.; Figueiredo, Rejane M. da C.; Venson, Elaine (iSys - Journal of Information Systems, 2018)
Context: Digital transformation is changing the industry and the way information technology (IT) is used. Most programs are already written by end users who know the business and need to meet goals with IT, although the governance established is not always adequate. It becomes crucial to understand how to decentralize the IT function to end users in order to prepare the organization for the challenges and opportunities of the 21st century. Objective: Based on a socio-technical perspective, this paper investigates how organizations decentralize IT with the adoption of End-User Development (EUD). Method: Two case studies were conducted in organizations that have been looking for EUD decentralization at least for the last 3 years. A conceptual framework for case analysis was described. Results: Previous maturity in IT governance was an important factor in the ability to decentralize by using EUD, although both cases have not achieved a high degree of decentralization yet. Shadow IT remained in the two cases. None of the two organizations have sought innovation with decentralization initiatives, although this is a fundamental view of the IT function in the 21st century.